2009
DOI: 10.1007/978-3-642-02164-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Foraging for Better Deployment of Replicated Service Components

Abstract: Abstract. Our work focuses on distributed software services and their requirements in terms of system performance and dependability. We target the problem of finding optimal deployment mappings involving multiple services, i.e. mapping service components in the software architecture to the underlying platforms for best possible execution. We capture important non-functional requirements of distributed services, regarding performance and dependability. These models are then used to construct appropriate cost fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…We observed that the smaller domains, e.g. d 3 , d 4 , were overloaded compared to the rest due to φ 1 , but generally replicas were placed quite evenly, showing that cooperation between the species worked.…”
Section: Simulation Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…We observed that the smaller domains, e.g. d 3 , d 4 , were overloaded compared to the rest due to φ 1 , but generally replicas were placed quite evenly, showing that cooperation between the species worked.…”
Section: Simulation Resultsmentioning
confidence: 83%
“…However, Fernandez-Baca [3] showed that the general module allocation problem is NP-complete except for certain communication configurations, thus heuristics are required to obtain solutions efficiently. This paper extends our previous work to find optimal deployment mappings [4], [5] based on a heuristic optimization method called the Cross-Entropy Ant System (CEAS). The strengths of the CEAS method is its capability to account for multiple parameters during the search for optimal deployment mappings [6].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our previous work [8] has focused on finding efficient mappings within relatively small scale clusters; and we experimented with different pheromone encodings for improving scalability in [7]. We have targeted a decentralized solution to avoid the burden of maintaining centralized databases and to eliminate performance and dependability bottlenecks.…”
Section: Related Workmentioning
confidence: 98%
“…This value is essentially an encoding of the VM instance mapping mn,r at node n in iteration r. Hence, the pheromone database must be able to store pheromone values that encode the various deployment configurations for various services. Three possible pheromone encoding techniques are discussed and evaluated in [8]; herein the best encoding is used.…”
Section: Cross Entropy Ant System For Replica Deploymentmentioning
confidence: 99%